Use of Animation in Character Education and Students' Mathematics Understanding - Nurhafida Rahmania; Fifi Alfiani; Nurwahida Nurwahida (Pancaran Pendidikan, 2021)
Use of Animation in Character Education and Students' Mathematics Understanding. This research development aims to make mathematics learning more innovative by using animation media. This research is for 4th grade elementary school level on circle material. Besides focusing on student learning, this research also focuses on character education. The method used in this research is classroom action research. The stages of development in this study began with planning, then action, observation, then reflection. Based on the trial results, there are revisions that must be corrected. The results of the study showed that the developed media had met the eligibility criteria and had met the requirements for use as learning media. The conclusions of the results of this study were seen based on the expert trial questionnaire.